A Case Report of Wound Infection Caused by Mycobacterium porcinum - Chen Q; Xu Y; Lin J; Zhou Q; Zhou H (Infection and Drug Resistance)
Qiyu Chen,1,* Yuxin Xu,1,* Jiali Lin,1,* Qiaoling Zhou,1,* Houqing Zhou2 1Department of Clinical Laboratory, Fuwai Hospital Chinese Academy of Medical Sciences, Shenzhen, People’s Republic of China; 2Department of Clinical Research and Epidemiology, Shenzhen Institute for Cardiovascular Disease, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Houqing Zhou, Department of Clinical Research and Epidemiology, Shenzhen Institute for Cardiovascular Disease, No. 12, Langshan Road, Nanshan District, Shenzhen, 518000, People’s Republic of China, Tel +86 821 800 28-8513, Email kyzhb@fuwaisz.cnBackground: Mycobacterium porcinum is a rapidly growing non-tuberculous mycobacterium that requires 3 to 5 days of cultivation for colonies to become visible to the naked eye, with most exhibiting vigorous growth during this initial week. It does not readily grow in standard bacterial culture conditions, posing challenges that often result in missed or incorrect diagnoses, and necessitating an extended course of anti-infective treatment.Case Presentation: This case report describes a rare instance of wound infection caused by Mycobacterium porcinum in a 64-year-old female patient who underwent mitral valve bioprosthesis replacement and temporary cardiac pacemaker implantation. In the postoperative period, the patient exhibited signs of infection, including elevated leukocyte count and neutrophil percentage, along with serous discharge from the surgical wound. Mycobacterium porcinum was definitively identified using 16sRNA gene sequencing. The patient responded well to a combination therapy consisting of amikacin, azithromycin, and moxifloxacin, complemented by surgical debridement.Conclusion: Rapidly growing mycobacteria, which require extended cultivation periods for visible colony formation, often result in underdetection. The atypical presentation of clinical symptoms can further delay the initiation of appropriate antibiotic therapy. This case underscores the critical role of prolonged cultivation time in detecting rapidly growing mycobacteria and highlights the importance of confirming genuine infections and the precision of clinical medication based on clinical symptoms and treatment outcomes.Keywords: Mycobacterium porcinum, wound infection, postoperative complications, non-tuberculous mycobacteria, antimicrobial therapy, case report